Effect of unsaturated fatty acids on myocardial performance, metabolism and morphology - Pinotti, M. F.; Silva, MDP; Sugizaki, M. M.; Diniz, Y. S.; Sant'Ana, L. S.; Aragon, F. F.; Padovani, Carlos Roberto [UNESP]; Novelli, ELB; Cicogna, Antonio Carlos [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2006)
Diets rich in saturated fatty acids are one of the most important causes of atherosclerosis in men, and have been replaced with diets rich in unsaturated fatty acids (UFA) for the prevention of this disorder. However, the effect of UFA on myocardial performance, metabolism and morphology has not been completely characterized. The objective of the present investigation was to evaluate the effects of a UFA-rich diet on cardiac muscle function, oxidative stress, and morphology. Sixty-day-old male Wistar rats were fed a control (N = 8) or a UFA-rich diet (N = 8) for 60 days. Myocardial performance was studied in isolated papillary muscle by isometric and isotonic contractions under basal conditions after calcium chloride (5.2 mM) and ss-adrenergic stimulation with 1.0 mu M isoproterenol. Fragments of the left ventricle free wall were used to study oxidative stress and were analyzed by light microscopy, and the myocardial ultrastructure was examined in left ventricle papillary muscle. After 60 days the UFA-rich diet did not change myocardial function. However, it caused high lipid hydroperoxide (176 +/- 5 vs 158 +/- 5, P < 0.0005) and low catalase (7 +/- 1 vs 9 +/- 1, P < 0.005) and superoxide-dismutase (18 +/- 2 vs 27 +/- 5, P < 0.005) levels, and discrete morphological changes in UFA-rich diet hearts such as lipid deposits and mitochondrial membrane alterations compared to control rats. These data show that a UFA-rich diet caused myocardial oxidative stress and mild structural alterations, but did not change mechanical function.
Keywords: fatty acids; cardiac function; oxidative stress; morphology; catalase; superoxide dismutase